A cost-efficient DC active load laboratory solution - Santoro, Danilo; Delmonte, Nicola; Cova, Paolo; Toscani, Andrea (Frontiers in Energy Research, 2022)
The increased use of DC renewable energy resources and DC storage systems, combined with the necessary reduction of energy waste, is boosting the development of DC smart grids. In this scenario, DC load emulation is of great importance. From the hardware point of view, DC buses stability of smart grids and the different DC/DC converter topologies have to be tested. From the software point of view, smart grid strategies and job schedulers must be tested with different power absorption profiles. Moreover, DC load emulation can be useful for many other purposes, such as battery characterization, power supply testing, photovoltaic I-V curve measurements, etc. In this work, a cost-efficient DC active load solution is proposed. The principle of the circuit topology is a buck-boost-derived converter. This solution can be implemented in a laboratory and sized considering the required voltage, current, and absorbed power ratios. Both simulation and experimental results are shown on a 400 W prototype. Thermal and electrical results validate the simulation model and the active load feasibility.